AL-MUSYKILAH AL-IQTIṢÂDIYAH DAN TIME VALUE OF MONEY DALAM KITAB AL-TAFSÎR AL-IQTIṢÂDÎ LI AL-QUR'ÂN AL-KARÎM KARYA RAFÎQ YÛNUS AL-MAṢRÎ - Didin Baharuddin (IAIN Ambon, 2017)
This paper discusses the economic problems and the time value of money contained in the book Al-Tafsir al-Iqtiṣâdî li Al-Quran Al-Karîm works Yunus Rafiq Al-Masri. The book Al-Tafsir al-Iqtiṣâdî li Al-Quran Al-Karîm an interpretation of contemporary books written by an economist (practitioners and academics), so that the economic approach is very strong in the book of this interpretation, which is not found in the books of other commentators , The approach to be distinctive in the book of commentary makes the Koran as problem solving for the dynamics of the public indefinitely. This paper will discuss the interpretation of Rafiq Yunus Al-Masri about the verses that contain the terms of the economy (al-Musykilah Al-Iqtiṣâdiyah) or economic problems and the time value of money. Keywords: term economy, time value of money, Tafsîr al-Iqtiṣâdî li Al-Qur'ân Al-Karîm